Aloe vera: A short review - Surjushe Amar; Vasani Resham; Saple D (Wolters Kluwer Medknow Publications, 2008)
Aloe vera is a natural product that is now a day frequently used in the field of cosmetology. Though there are various indications for its use, controlled trials are needed to determine its real efficacy. The aloe vera plant, its properties, mechanism of action and clinical uses are briefly reviewed in this article.